Altered Expression of Mitochondrial NAD+ Carriers Influences Yeast Chronological Lifespan by Modulating Cytosolic and Mitochondrial Metabolism - Orlandi, Ivan; Stamerra, Giulia; Vai, Marina (Frontiers in Genetics, 2018)
Nicotinamide adenine dinucleotide (NAD+) represents an essential cofactor in sustaining cellular bioenergetics and maintaining cellular fitness, and has emerged as a therapeutic target to counteract aging and age-related diseases. Besides NAD+ involvement in multiple redox reactions, it is also required as co-substrate for the activity of Sirtuins, a family of evolutionary conserved NAD+-dependent deacetylases that regulate both metabolism and aging. The founding member of this family is Sir2 of Saccharomyces cerevisiae, a well-established model system for studying aging of post-mitotic mammalian cells. In this context, it refers to chronological aging, in which the chronological lifespan (CLS) is measured. In this paper, we investigated the effects of changes in the cellular content of NAD+ on CLS by altering the expression of mitochondrial NAD+ carriers, namely Ndt1 and Ndt2. We found that the deletion or overexpression of these carriers alters the intracellular levels of NAD+ with opposite outcomes on CLS. In particular, lack of both carriers decreases NAD+ content and extends CLS, whereas NDT1 overexpression increases NAD+ content and reduces CLS. This correlates with opposite cytosolic and mitochondrial metabolic assets shown by the two types of mutants. In the former, an increase in the efficiency of oxidative phosphorylation is observed together with an enhancement of a pro-longevity anabolic metabolism toward gluconeogenesis and trehalose storage. On the contrary, NDT1 overexpression brings about on the one hand, a decrease in the respiratory efficiency generating harmful superoxide anions, and on the other, a decrease in gluconeogenesis and trehalose stores: all this is reflected into a time-dependent loss of mitochondrial functionality during chronological aging.